Validation of POLDER GRASP aerosol optical retrieval over China using SONET observations. (May 2020) - Wei, Yuanyuan; Li, Zhengqiang; Zhang, Ying; Chen, Cheng; Dubovik, Oleg; Zhang, Yang; Xu, Hua; Li, Kaitao; Chen, Jie; Wang, Haofei; Ge, Bangyu; Fan, Cheng
Highlights: A statistical comparison of GRASP total AOD, fine mode AOD and Fine Mode Fraction (FMF) with Sun–Sky Radiometer Observation Network (SONET) products over China was conducted. Both GRASP «models» and GRASP «high-precision» products were evaluated at 8 SONET sites. Both SONET-SDA and SONET-IP retrievals were compared with GRASP fine mode AOD. The comparison between MODIS-FMF and GRASP-FMF was conducted. Abstract: Monitoring fine mode aerosol pollutants is one of priorities in national environmental programs. Aerosol Optical Depth (AOD) and fine mode AOD are key parameters for estimation of particulate matter. POLDER/GRASP retrieval provides probably the most detailed aerosol products globally for 2005 – 2013. Current studies are focused on understanding the value of new satellite products for potential monitoring of air quality over China. As part of this objective, the quantitative evaluation of the products over China, a statistical comparison of total AOD, fine mode AOD and Fine Mode Fraction (FMF) with Sun–Sky Radiometer Observation Network (SONET) products is conducted. Two of available POLDER aerosol products: GRASP «models» and «high-precision» were evaluated at 8 SONET sites over China in this study. The results show the best agreement of the total AOD at 490 nm from «models» approach with AOD (500 nm) from SONET with correlation coefficient of 0.96, slope of 0.9, RMSE of 0.14 and bias (intercept) of 0.04, with about 76% of retrievals inside of Gfrac ranges. The validation results of the fine mode AOD at 490 nm with AOD the fine mode SONET-SDA product (500 nm) are quite comparable for both «high-precision» and «models» approaches, with slightly better results for «high-precision» data showing correlation coefficient of 0.95, slope of 0.78, RMSE of 0.14 and bias (intercept) of 0.07, with about 68% of retrievals inside of Gfrac ranges. The analysis is demonstrated that POLDER/GRASP results are one of most suitable aerosol products for characterization of FMF (Fine Mode Fraction) of aerosol. For example, compared with MODIS, the FMF from POLDER/GRASP is significantly closer to SONET-SDA FMF, with Gfrac increasing from 16.75% (MODIS) to 62.35% (POLDER/GRASP). Moreover, there is a clear similarity of spatial distribution of the fine mode AOD from GRASP with ground-level PM2.5 observations.